Contagion effects of the Silicon Valley Bank run - Dong Beom Choi; Paul Goldsmith-Pinkham; Tanju Yorulmazer (Koç University-TÜSIAD Economic Research Forum (ERF), 2023)
This paper analyzes the contagion effects associated with the failure of Silicon Valley Bank (SVB) and identifies bank-specific vulnerabilities contributing to the subsequent declines in banks' stock returns. We find that uninsured deposits, unrealized losses in held-to-maturity securities, bank size, and cash holdings had a significant impact, while better-quality assets or holdings of liquid securities did not help mitigate the negative spillovers. Interestingly, banks whose stocks performed worse post SVB also had lower returns in the previous year following Federal Reserve interest rate hikes. The stock market partially anticipated risks associated with uninsured deposit reliance, but did not price in unrealized losses due to interest rate hikes nor risks linked to bank size. While mid-sized banks experienced particular stress immediately after the SVB failure, over time negative spillovers became widespread except for the largest banks.
Keywords: G01; G21; G14; G28; E58; E43; 330; Contagion; Banking crisis; Bank run; Systemic risk; Interest rate risk; Hidden losses; Held-to-maturity; Bankinsolvenz; Ansteckungseffekt; Bankenkrise; Bankrisiko; Finanzkrise; USA